2021
DOI: 10.3389/fimmu.2021.735497
|View full text |Cite
|
Sign up to set email alerts
|

SPINK7 Recognizes Fungi and Initiates Hemocyte-Mediated Immune Defense Against Fungal Infections

Abstract: Serine protease inhibitors of Kazal-type (SPINKs) were widely identified in vertebrates and invertebrates, and played regulatory roles in digestion, coagulation, and fibrinolysis. In this study, we reported the important role of SPINK7 in regulating immune defense of silkworm, Bombyx mori. SPINK7 contains three Kazal domains and has 6 conserved cysteine residues in each domain. Quantitative real-time PCR analyses revealed that SPINK7 was exclusively expressed in hemocytes and was upregulated after infection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…We further found that KPI5 binds to pathogens and their PAMPs but does not inhibit pathogen growth. Unlike KPI5, silkworm low molecular weight protease inhibitors SPINK7 (Kazal-type) and BmSPI51 (Kunitz-type) directly inhibit fungal growth by binding to β -d-glucan on the fungal surface ( 30 , 38 ). Insect immune processes mainly include: immune recognition, signal transmission, and effector production ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further found that KPI5 binds to pathogens and their PAMPs but does not inhibit pathogen growth. Unlike KPI5, silkworm low molecular weight protease inhibitors SPINK7 (Kazal-type) and BmSPI51 (Kunitz-type) directly inhibit fungal growth by binding to β -d-glucan on the fungal surface ( 30 , 38 ). Insect immune processes mainly include: immune recognition, signal transmission, and effector production ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The binding between rKPI5 protein and PAMPs was measured using an enzyme-linked immunosorbent assay (ELISA) according to previous studies ( 37 , 38 ), with slightly modifications. Briefly, 5 μg LPS, PGN, and ZYM were dissolved in coating solution (0.5 M carbonate buffer, pH 9.8), added to a 96-well microtiter plate, and incubated at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…We further found that KPI5 binds to pathogens and their PAMPs but does not inhibit pathogen growth. Unlike KPI5, silkworm low molecular weight protease inhibitors SPINK7 (Kazal-type) and BmSPI51 (Kunitztype) directly inhibit fungal growth by binding to b-d-glucan on the fungal surface (30,38). Insect immune processes mainly include: immune recognition, signal transmission, and effector production (48).…”
Section: Discussionmentioning
confidence: 99%
“…The binding between rKPI5 protein and PAMPs was measured using an enzyme-linked immunosorbent assay (ELISA) according to previous studies (37,38), with slightly modifications. Briefly, 5 mg LPS, PGN, and ZYM were dissolved in coating solution (0.5 M carbonate buffer, pH 9.8), added to a 96-well microtiter plate, and incubated at 4°C overnight.…”
Section: Microbial and Pamps Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation